Twenty years of digital preservation: the state of the art observed from strategic planning, models, standards, plans and policies (2000-2022) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Since the publication of ISO 16363:2012, digital preservation practices have been experiencing a new perspective on the longevity of digital assets in relation to Digital Repositories. However, there is still a long way to go before Digital Preservation reaches a more advanced level in Brazil. In this context, this article aims to identify the preservation practices that have been used to guarantee the longevity of digital stocks, from a national and international perspective, in the last two decades. The methodology for developing the state of the art in this study is based on the qualitative and quantitative survey of descriptive research, based on the use of the bibliometric method. The systematic review of the literature pointed out that, currently, Digital Preservation is moving towards a stage of maturity, but there is still a long way to go to reach this goal. Lots of Universities in Brazil and around the world, they still do not have a digital preservation policy that ensures the reliability of their Digital Repositories. Without defined policies, there is no way to plan and without planning, strategies continues to be applied in a random way.
Keywords: models for digital preservation; standards for digital preservation; digital preservation strategies; policies for digital preservation; digital preservation plans